2020
DOI: 10.3390/catal10020211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stannic Species Modification on the Acidity of Silicalite-1 and Its Enhancement in Transforming Ethylenediamine to Heterocyclic Amines

Abstract: In this study, a series of SnO 2 modified zeolite catalysts (Snx-S-1; x is the weight percentage of Sn) were prepared with SnCl 2 and a defective Silicalite-1 (S-1) zeolite via facile deposition-precipitation method. It was found that the stannic species modified all-silica zeolite catalysts were active for the intermolecular condensation of ethylenediamine (EDA) to 1, 2-Diazabicyclo [2, 2, 2] octane (TEDA) and piperazine (PIP). The best catalyst Sn6-S-1 (6 wt.% Sn loading) showed 86% EDA conversion and 93% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The silanol nests present in a defective silicalite-1 were found to provide acidity for ethylenediamine (EDA) conversion, meanwhile this acidity could not ensure alone a high conversion. 175,176 In the case of the MFI zeolite containing Ti (TS-1), silanol groups in the vicinity of Ti sites were pointed as the ones responsible by the EDA condensation, rather than the Lewis acid sites from Ti(V). The higher acidity of silanols in TS-1 compared to silicalite-1 was related to an electronic effect or structural deformation generated by the Ti atom, as in Fig.…”
Section: Fig 26 Schematic Representation Of the H-bonded Silanol Comp...mentioning
confidence: 99%
“…The silanol nests present in a defective silicalite-1 were found to provide acidity for ethylenediamine (EDA) conversion, meanwhile this acidity could not ensure alone a high conversion. 175,176 In the case of the MFI zeolite containing Ti (TS-1), silanol groups in the vicinity of Ti sites were pointed as the ones responsible by the EDA condensation, rather than the Lewis acid sites from Ti(V). The higher acidity of silanols in TS-1 compared to silicalite-1 was related to an electronic effect or structural deformation generated by the Ti atom, as in Fig.…”
Section: Fig 26 Schematic Representation Of the H-bonded Silanol Comp...mentioning
confidence: 99%
“…51−55 Additionally, a weak band at 3675 cm −1 corresponding to weakly hydrogen-bonded vicinal silanols was also discernible. 56,57 After the doping of Fe atoms, the broad band with the maximum at 3438 cm −1 increased prominently, whereas the weak band at 3675 cm −1 was almost unaltered. The absorption band at 3726 cm −1 was also enhanced for 500-Fe-silicalite-1 and 100-Fe-silicalite-1, but it was inconspicuous for 2000-Fesilicalite-1 and 1000-Fe-silicalite-1.…”
Section: Resultsmentioning
confidence: 99%
“…The IR spectra under a vacuum via outgassing (Figure B) showed that there were two characteristic absorption bands with maxima at 3726 and 3438 cm –1 assigned to the terminal silanols located within the interior surface of zeolite and hydrogen-bonded groups of silanol nests, respectively. Additionally, a weak band at 3675 cm –1 corresponding to weakly hydrogen-bonded vicinal silanols was also discernible. , After the doping of Fe atoms, the broad band with the maximum at 3438 cm –1 increased prominently, whereas the weak band at 3675 cm –1 was almost unaltered. The absorption band at 3726 cm –1 was also enhanced for 500-Fe-silicalite-1 and 100-Fe-silicalite-1, but it was inconspicuous for 2000-Fe-silicalite-1 and 1000-Fe-silicalite-1.…”
Section: Resultsmentioning
confidence: 99%